UNMASKING COMPARATIVE BIAS OF GENDER IN GRAD ENGLISH SYLLABUS: FEMINIST CRITICAL DISCOURSE ANALYSIS - Muhammad Iqbal; Rizwana Ahmad; Riaz Hussain (International Journal of Contemporary Issues in Social Sciences, 2024)
The current study explores the representation of women in English syllabus at graduation-level employing feminist critical discourse analysis (CDA) within the theoretical framework of the Fairclough 3D Model. Feminist CDA focusses on the inequitable representation of female figure in language practices and gendered power dynamics. It highlights how differently women are portrayed in terms of their restricted domestic roles. It is a fact that curriculum has a significant influence on students development and worldview. Critical Discourse Analysis (CDA) is used in to determine if the English curriculum at the graduation level upholds traditional stereotypes or portrays women in positions that are gender-neutral and career-oriented. Through this study, the researcher endeavors to draw the attention of the syllabus designers towards this critical issue of female identity.